2001
DOI: 10.1007/bf02708645
|View full text |Cite
|
Sign up to set email alerts
|

Spectral, magnetic and biological studies of 1,4-dibenzoyl-3-thiosemicarbazide complexes with some first row transition metal ions

Abstract: The ligand 1,4-dibenzoyl-3-thiosemicarbazide (DBtsc) forms complexes [M(DBtsc-H)(SCN)] [M = Mn(II), Co(II) or Zn(II)], [M(DBtsc-H)(SCN)(H 2 O)] [M = Ni(II) or Cu(II)], [M(DBtsc-H)Cl] [M = Co(II), Ni(II), Cu(II) or Zn(II)] and [Mn(DBtsc)Cl 2 ], which have been characterized by elemental analyses, magnetic susceptibility measurements, UV/Vis, IR, 1 H and 13 C NMR and FAB mass spectral data. Room temperature ESR spectra of the Mn(II) and Cu(II) complexes yield values, characteristic of tetrahedral and square … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Semicarbazones and thiosemicarbazones can form complexes with metals and several of them have exhibit biological activity (particularly antimicrobial and antitumor activity have been reported) [5] [6] [7]. Additionally, they have been used as corrosion inhibitors of certain alloys [8].…”
Section: Nh Phmentioning
confidence: 99%
“…Semicarbazones and thiosemicarbazones can form complexes with metals and several of them have exhibit biological activity (particularly antimicrobial and antitumor activity have been reported) [5] [6] [7]. Additionally, they have been used as corrosion inhibitors of certain alloys [8].…”
Section: Nh Phmentioning
confidence: 99%
“…For the various biological activities of bis-thiosemicarbazones, see: Singh et al (2001); Offiong & Martelli (1997). For general synthesis and assessment of the pharmaceutical properties of thiosemicarbazone scaffold compounds, see: Greenbaum et al (2004); Finch et al (1999); Wilson et al (1974); Du et al (2002) Marzano et al (2009).…”
Section: Related Literaturementioning
confidence: 99%
“…Because of variable bonding modes, biological implications, and structural diversity of thiosemicarbazones [14][15][16], they have been used as drugs and are reported to possess a wide variety of biological activities against bacteria, fungi, and certain types of tumor [17,18]. It has been reported that the presence of bulky groups at N4 of the thiosemicarbazone moiety greatly enhances biological activity [19].…”
Section: Introductionmentioning
confidence: 99%